On existence of private unemployment insurance with advance information on future job losses - Piotr Denderski; Christian A. Stoltenberg (Tinbergen Institute, 2021)
We study the existence of a profitable unemployment insurance market in a dynamic economy with adverse selection rooting in information on future job losses. The new feature of the model is that the insurer and workers interact repeatedly. Repeated interactions make it possible to threaten workers with exclusion from future insurance benefits after a default on insurance premia. With exclusion, not only the insurance against the fundamental risk, but also against future bad news about job losses matters. In contrast to conventional wisdom, we find that private unemployment insurance in the US can be profitable for a relatively short exclusion length of one year. To stimulate the emergence of a private unemployment insurance market, policy makers can facilitate the creation of a registry that archives past defaults on insurance premia.
Keywords: D82; D86; G22; J65; 330; Advance information; subjective expectations; adverse selection; unemployment insurance; repeated interactions; dynamic contracts